Does Malachi 1:2-3 Teach Double Predestination? - Philip Suciadi Chia; Juanda Juanda (Jurnal Didaskalia, 2021)
The term ‘double predestination’ simply means that, just as God predestines some, but not all, to eternal salvation, so he predestines others to eternal punishment; this second part of ‘double predestination’, God's appointment of all but the elect unto eternal destruction, is sometimes called ‘reprobation’; and those who are not the elect are thus called the ‘reprobate’.The object of Malachi was in reminding the Jews that they were loved and chosen by God; it was, that he might the more amplify their ingratitude for having rendered such an unworthy reward for so great a favor of God: as he had preferred them to all other nations, he had justly bound them to perpetual obedience. With the inductive method, we will present a more objective truth of Scripture. We will not only explain the truth of the Bible would conclude (correct interpretation), but also accompanied by the evidence and arguments of the conclusions. In conclusion, the meaning of hate in this context is God hated Esau, the absence of affection, because he is a sinful people therefore Yahweh opposed and kept distant from him (have no relationship). Based on this meaning, we can summarize that this verse (Mal. 1:3) doesn’t teach about reprobation that God has predestined Esau to go to eternal destruction because Yahweh hated him beforehand but Lord indeed hated Edomites because they are sinful people.